Role of parasitic vaccines in integrated control of parasitic diseases in livestock - Sharma, Neelu (Vet World, 2015)
Parasitic infections adversely affect animal’s health and threaten profitable animal production, thus affecting the economy of our country. These infections also play a major role in the spread of zoonotic diseases. Parasitic infections cause severe morbidity and mortality in animals especially those affecting the gastrointestinal system and thus affect the economy of livestock owner by decreasing the ability of the farmer to produce economically useful animal products. Due to all these reasons proper control of parasitic infection is critically important for sustained animal production. The most common and regularly used method to control parasitic infection is chemotherapy, which is very effective but has several disadvantages like drug resistance and drug residues. Integrated approaches to control parasitic infections should be formulated including grazing management, biological control, genetic resistance of hosts, and parasitic vaccines. India ranks first in cattle and buffalo population, but the majority of livestock owners have fewer herds, so other measures like grazing management, biological control, genetic resistance of hosts are not much practical to use. The most sustainable and economical approach to control parasitic infection in our country is to vaccinate animals, although vaccines increase the initial cost, but the immunity offered by the vaccine are long lived. Thus, vaccination of animals for various clinical, chronic, subclinical parasitic infections will be a cheaper and effective alternative to control parasitic infection for long time and improve animal production.